2006
DOI: 10.1530/rep.1.00946
|View full text |Cite
|
Sign up to set email alerts
|

Reduced recruitment and survival of primordial and growing follicles in GH receptor-deficient mice

Abstract: GH influences female fertility. The goal of the present study was to obtain more insight into the effect of loss of GH signalling, as observed in humans suffering from Laron syndrome, on ovarian function. Therefore, serial paraffin sections of ovaries of untreated and IGF-I-treated female GH receptor knock-out (GHR/GHBP-KO) mice were examined to determine the follicular reserve and the percentage of follicular atresia in each ovary. Our observations demonstrate that the amount of primordial follicles was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 54 publications
4
66
1
2
Order By: Relevance
“…Therefore, the higher expression of Foxo3a indicates that follicles could be trapped in the primordial stage. This hypothesis agrees with histological observations in long-living GH-resistant GHRKO mice, where a higher number of follicles in the primordial stage are observed concomitantly with fewer follicles in the primary, secondary, and tertiary stages (Slot et al 2006). A recent study has demonstrated that oocyte expression of a constitutively active form of Foxo3 in a transgenic mouse model is associated with the preservation of the ovarian reserve (Pelosi et al 2013) and, therefore, can be related to an ovarian phenotype characteristic of younger mice as observed in GHRKO mice in the current and previous studies (Sluczanowska- Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, the higher expression of Foxo3a indicates that follicles could be trapped in the primordial stage. This hypothesis agrees with histological observations in long-living GH-resistant GHRKO mice, where a higher number of follicles in the primordial stage are observed concomitantly with fewer follicles in the primary, secondary, and tertiary stages (Slot et al 2006). A recent study has demonstrated that oocyte expression of a constitutively active form of Foxo3 in a transgenic mouse model is associated with the preservation of the ovarian reserve (Pelosi et al 2013) and, therefore, can be related to an ovarian phenotype characteristic of younger mice as observed in GHRKO mice in the current and previous studies (Sluczanowska- Fig.…”
Section: Discussionsupporting
confidence: 92%
“…This evidence suggests that GH is important for maximal reproductive efficiency; however, systemic IGF-I is essential for N follicle development, and females are not able to reproduce in its absence. Additionally, GHRKO females have an increased number of primordial follicles and a reduced number of healthy antral follicles Slot et al 2006), which can explain the reduced ovulation rate. However, treating GHRKO females with IGF-I decreases the number of primordial follicles and increases the number of healthy antral follicles (Slot et al 2006), suggesting that IGF-I-induced signaling promotes primordial follicle activation and antral follicle survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our data show that endocrine IGF1 is capable of supporting reproductive performance all by itself. Aside of mechanistic relationships, which will undoubtedly turn out to be very complex, our results in regard to female LIP reproduction are consistent with observations on female Ghr null mice (30). Although fertile, these mutants exhibit delayed sexual maturation and produce small-size litters, presumably because of reduced ovulation rates.…”
Section: Discussionsupporting
confidence: 89%
“…Their ovaries contain increased numbers of primordial and atretic follicles, while the numbers of healthy growing antral follicles is reduced. This defect was rescued, and the respective numbers of follicles were reversed, following IGF1 administration for two weeks (30).…”
Section: Discussionmentioning
confidence: 98%